Accuracy Investigation of PPP Method Versus Relative Positioning Using Different Satellite Ephemerides Products Near/Under Forest Environment - Taylan Ocalan; Bahattin Erdogan; Nursu Tunalioglu; Utkan Mustafa Durdag (Earth Sciences Research Journal)
In recent years, due to the increase in providers of orbit and clock corrections of satellites for data evaluation in real-time and post-processing the method of Precise Point Positioning (PPP) using measurements of Global Navigation Satellite System (GNSS) and Web-based online positioning services have become widespread. Owing to some advantages, such as work-duration and cost-effectiveness, many of users have implemented PPP method instead of the traditional relative positioning method for several applications. On GNSS applications the quality of satellite ephemerides products used for data evaluation is a significant factor that affects the results in post-processing solutions either applying relative or PPP methods on analyses. These products, classified as ultra-rapid, rapid and final orbits, are regularly provided by several national and international organizations to the users. In this paper, the accuracy of PPP method has been studied comparing the outcomes from various online Web services using different software and satellite ephemerides products. For this purpose, three test points were established in a place with completely free satellite visibility (AC01) and on the other two places with partially (YC01) and vastly (KC01) prevention of satellite signals near and within a forest area at Campus of Davutpaşa of the Yildiz Technical University in Istanbul. At these stations, static observations have been conducted with a time span of 6 hours on 4th May 2015. The dataset collected using Topcon HiperPro receiver, a receiver for GPS and GLONASS data, was evaluated manually by means of the Bernese v5.2 (BSW) and GIPSY-OASIS v6.3 (Gipsy) scientific software. Moreover, the GNSS data were also proceeded using six different Web-based online services (AUSPOS, OPUS, CSRS-PPP, APPS, GAPS, Trimble-RTX) with ultra-rapid, rapid and final satellite ephemerides products. For the station with free satellite visibility (AC01), the analyses of outcomes indicate a coordinate accuracy of 1 cm for Web-based and manual data processing. That suggests relative good quality of orbit and clock corrections of satellites used by online data processing services for PPP. Furthermore, for station with partially (YC01) prevention of satellite signals, manual solutions have approximately 1 cm coordinate accuracies for n, e and u components. Moreover, when we compare the results among Web-based services, AUSPOS in relative solution and TrimbleRTX in PPP solution provides the best results. Here, one must emphasize that Trimble-RTX is a Web-based processing service for GNSS data (GPS, GLONASS, BeiDou, and QZSS) and operates an own global network of approximately 100 stations around the world for this purpose. For station with vastly (KC01) prevention of satellite signals, the best solutions were provided by APPS and CSRS-PPP using PPP approach among the Web-based services. Here, Trimble-RTX could not produce any solution. These results could demonstrate the benefit of multi-constellation of GNSS in the areas with limited satellite visibility because of increasing of the number of measurements.